Inteligencia emocional y hábitos de estudio en los estudiantes de bachillerato de la Unidad Educativa “Hispanoamérica” de la ciudad de Riobamba, periodo 2019-2020 - Auqui Rivera, Tania Gissela (2021)
The present research entitled: "Emotional intelligence and study habits in high school students of the" Hispanoamérica "Educational Unit of the city of Riobamba, period 2019-2020, aimed to determine the relationship between emotional intelligence and study habits in aforementioned students, where the beneficiaries were 154 students distributed in first, second and third year of high school. The methodology used has a mixed approach, the design is non-experimental, the type of research by level or scope was correlational, by the basic objective, by the field location and by the type of cross-sectional study. It was carried out using two instruments, the TMMS-24 emotional intelligence test and the CASM-85 Study Habits Inventory. The TMMS-24 test aims to evaluate the meta knowledge of emotional states, it consists of a questionnaire of 24 questions divided into three dimensions: emotional perception, understanding of feelings and emotional regulation. The CASM-85 Study Habits Inventory aims to measure and diagnose students' study habits, it consists of a questionnaire of 53 questions divided into 5 dimensions: How do you study? How do you do your homework? How do you prepare your exams? How do you listen to the classes? and What accompanies your moments? The results showed that there is no correlation between emotional intelligence and study habits in high school students from the "Hispanoamérica" Educational Unit.